2015
DOI: 10.1016/j.resmic.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Host adaption to the bacteriophage carrier state of Campylobacter jejuni

Abstract: The carrier state of the foodborne pathogen Campylobacter jejuni represents an alternative life cycle whereby virulent bacteriophages can persist in association with host bacteria without commitment to lysogeny. Host bacteria exhibit significant phenotypic changes that improve their ability to survive extra-intestinal environments, but exhibit growth-phase-dependent impairment in motility. We demonstrate that early exponential phase cultures become synchronised with respect to the non-motile phenotype, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 67 publications
(103 reference statements)
0
28
0
Order By: Relevance
“…Moreover, Campylobacter bacteriophage carrier state cultures also escape phage lysis by undergoing growth phase dependent motility attenuation as a response to phage association (Siringan et al, 2014). Whereas, flaA gene transcription is down-regulated in carrier state cultures, which likely accounts for their impaired mobility, flaB transcription is up-regulated, which based on the current data could be an adaption to limit phage infection leading to cell lysis (Brathwaite et al, 2015; Hooton et al, 2016). It is recognized that σ 54 is part of a group of transcriptional regulators termed class 1 genes that demonstrate hierarchical regulation of class 2 genes, which are fundamental for the formation of the flagellar secretory apparatus and code for the structural components of the basal body of the flagellum (Hendrixson and DiRita, 2003; Lertsethtakarn et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, Campylobacter bacteriophage carrier state cultures also escape phage lysis by undergoing growth phase dependent motility attenuation as a response to phage association (Siringan et al, 2014). Whereas, flaA gene transcription is down-regulated in carrier state cultures, which likely accounts for their impaired mobility, flaB transcription is up-regulated, which based on the current data could be an adaption to limit phage infection leading to cell lysis (Brathwaite et al, 2015; Hooton et al, 2016). It is recognized that σ 54 is part of a group of transcriptional regulators termed class 1 genes that demonstrate hierarchical regulation of class 2 genes, which are fundamental for the formation of the flagellar secretory apparatus and code for the structural components of the basal body of the flagellum (Hendrixson and DiRita, 2003; Lertsethtakarn et al, 2011).…”
Section: Discussionmentioning
confidence: 86%
“…We have noted instability in the FlhF(T368A) protein that may hinder recruitment of components required to affect the expression of downstream flagellar components, which may also provide an explanation as to the differential effects of mutants affected in FlhF GTPase activity (Balaban et al ., ), if the mutants also alter FlhF structural dependencies. The expression of the σ 28 and σ 54 dependent genes determined in this study for the flhF(T368A) complement relative to wild type C. jejuni PT14 are consistent with the transcriptome (RNA‐seq) study reported for a C. jejuni PT14CP30A carrier state culture (Brathwaite et al ., ). The exception to this is the expression of flaB, which is down regulated in the flhF(T368A) complement strain relative to wild type C. jejuni PT14, as compared to a 3‐fold up regulation reported for the C. jejuni PT14CP30A carrier state strain.…”
Section: Discussionmentioning
confidence: 97%
“…The exception to this is the expression of flaB, which is down regulated in the flhF(T368A) complement strain relative to wild type C. jejuni PT14, as compared to a 3‐fold up regulation reported for the C. jejuni PT14CP30A carrier state strain. Phage transcription indicative of the progression toward replication was evident in the carrier state cultures (0.2% of the total reads), and where the abundance of the major capsid protein transcripts represented > 95% of all the normalized read counts (Brathwaite et al ., ). We therefore posit that the up regulation of flaB in the carrier state C. jejuni is a consequence phage transcription/replication.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Brathwaite and colleagues, also noticed the decreased ability of biofilm-associated C. jejuni subpopulation, infected with lytic phages in CSLC, to colonize broilers. RNA-seq analysis found that the decreased fitness was due to down-regulation of important stress-response genes, including the major flagellar protein FlaA [79]. The conclusion drawn from these observations is that, due to the short lifespan of broilers, it is unclear how the dynamics of resistance continue.…”
Section: Resistance Due To Spontaneous Mutationsmentioning
confidence: 99%